Controlled synthesis of calcite/vaterite/aragonite and their applications as red phosphors doped with Eu3+ ions. Issue 20 (5th May 2017) - Dai, Yunzhi; Zou, Haifeng; Zhu, He; Zhou, Xiuqing; Song, Yanhua; Shi, Zhan; Sheng, Ye
Abstract : Vaterite/aragonite have been prepared in the presence of NaCMC and the polymorph-dependent luminescence properties of CaCO3 :Eu 3+ have been discussed. Abstract : Calcium carbonate (CaCO3 ) particles including three anhydrous polymorphs (calcite/vaterite/aragonite) have been prepared in the absence and presence of sodium carboxyl methylcellulose (NaCMC), which further serve as hosts to prepare the phosphors doped with Eu 3+ . The as-obtained samples were characterized by means of XRD, SEM, and PL techniques. The experimental results reveal that vaterite, as a less stable polymorph, will transform into calcite in aqueous solution without any additive. In contrast, NaCMC can induce the formation of vaterite phase at 50 °C and the formation of aragonite phase at 90 °C in aqueous solution. In addition, the polymorph-dependent luminescence properties of CaCO3 :Eu 3+ have been briefly studied by excitation spectra, emission spectra, PL decay curves and quantum yield.